2015
DOI: 10.1111/codi.12947
|View full text |Cite
|
Sign up to set email alerts
|

Autologous skeletal‐muscle‐derived cell injection for anal incontinence due to obstetric trauma: a 5‐year follow‐up of an initial study of 10 patients

Abstract: Autologous skeletal-muscle-derived cells to treat obstetric anal incontinence resulted in sustained improvement in incontinence episodes, physiological measurements of anal function and quality of life at 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 20 publications
(28 reference statements)
3
62
0
1
Order By: Relevance
“…this could be due to cell apoptosis because of the increased volume injected and decreased cytokines at the site of injection, or it is because the electrical stimulation was stopped on the same day. Recently, a human study evaluated electrical stimulation followed by autologous skeletal muscle-derived cell treatment and showed sustained improvement of quality of life at 5 years in patients with anal incontinence due to obstetric trauma, 33,34 which further strengthens the basis for this study.…”
Section: Discussionsupporting
confidence: 57%
“…this could be due to cell apoptosis because of the increased volume injected and decreased cytokines at the site of injection, or it is because the electrical stimulation was stopped on the same day. Recently, a human study evaluated electrical stimulation followed by autologous skeletal muscle-derived cell treatment and showed sustained improvement of quality of life at 5 years in patients with anal incontinence due to obstetric trauma, 33,34 which further strengthens the basis for this study.…”
Section: Discussionsupporting
confidence: 57%
“…This report by Romaniszyn et al [1] is among the first to independently confirm the clinical observations from Frudinger et al [5]. Romaniszyn et al's findings are particularly timely since Frudinger et al [6] just published a follow-up to their original clinical cohort documenting persistent improvements in patient symptoms for up to 5 years [6].…”
mentioning
confidence: 69%
“…To simplify the cell isolation and proliferation process, Mazzanti et al used freshly isolated minimally manipulated bone‐marrow derived mononuclear cells without expansion and found them to be as effective as in vitro expanded BM‐MSCs in the recovery of iatrogenic anal sphincter rupture 38. Muscle‐derived stem cell injections have been used in small pilot studies in women and the results are promising 39, 40, 41. Frudinger et al treated 10 patients with autologous myogenic stem cells and found a significant improvement in the AI symptoms at 1‐ and 5‐year controls.…”
Section: Discussionmentioning
confidence: 99%